ADVANCES IN THE TREATMENT OF METHANOL POISONING: A REVIEW OF CURRENT CLINICAL EVIDENCE - da Silva, Laura Leme de Araujo Rodrigues; Honório, Lara Tatyane Ferreira Santos; Beltrão, Clarissa Maria Tito; Fachin, Laércio Pol; de Almeida, Marília Timo Pinheiro; Correia, Isisnaldo Silva; de Carvalho, Hiago Cezar Rocha; Sanomia, Morgana Sayuri; Kague, Danielle Lumi; Ferreira, Caio de Lima; Siqueira, Thaila Raissa da Costa; da Costa, Lana Luísa Alves; et al. (Seven Editora, 2025)
Methanol poisoning is a serious global public health problem, associated with high morbidity and mortality rates and outbreaks related to the consumption of adulterated beverages. This study aimed to identify, analyze, and synthesize recent clinical evidence on treatment strategies for methanol poisoning, with an emphasis on therapeutic and organizational advances over the last decade. This is an integrative literature review, conducted according to the steps proposed by Whittemore and Knafl (2005). The search was conducted in the PubMed, SciELO, Scopus, and Consensus Database between November and December 2025, using the descriptors “methanol poisoning,” “treatment,” “fomepizole,” “ethanol therapy,” and “hemodialysis.” A total of 216 studies were identified, of which 12 met the inclusion criteria (publications between 2013 and 2025, full text, and clinical-therapeutic focus). The evidence points to fomepizole as the first-choice antidote and early hemodialysis as a determining factor in reducing mortality and neurological sequelae. Standardized clinical protocols and multidisciplinary teams contributed to greater effectiveness and speed of care. It is concluded that this review contributes to consolidating the clinical evidence on the treatment of methanol poisoning, providing support for evidence-based practice and the formulation of public policies focused on clinical toxicology. DOI: https://doi.org/10.56238/sevened2025.037-039